2011
DOI: 10.7600/jspfsm.60.379
|View full text |Cite
|
Sign up to set email alerts
|

Home Based Exercise Effects on Cognition in the Semi-Independent Elderly

Abstract: This study sought to determine whether aerobic exercise training affects cognitive functioning among semi-independent (> 75 years) and independent elderly people. Seventysix semi-independent and independent elderly subjects were divided into the following groups: semi-independent control (n = 16); semi-independent training (n = 13); independent control (n = 22); independent training (n = 25). During the 12-week intervention, subjects in both training groups performed a bench-stepping exercise at the intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…High-intensity exercise improves both cognitive and mental function [ 31 , 32 ], whereas moderate-intensity exercise is known to improve cognitive and mental function [ 33 , 34 ] through neurogenesis and neuroendocrine responses [ 35 , 36 ]. We adopted the 50% heart rate reserve (HRR) task, which is considered to be a moderate-intensity exercise as per ACSM’s Guidelines for Exercise Testing and Prescription [ 37 ], and employed a previously-reported step exercise using a low-height bench [ 33 ]. For the former intensity, we calculated the target heart rate using the formula: …”
Section: Methodsmentioning
confidence: 99%
“…High-intensity exercise improves both cognitive and mental function [ 31 , 32 ], whereas moderate-intensity exercise is known to improve cognitive and mental function [ 33 , 34 ] through neurogenesis and neuroendocrine responses [ 35 , 36 ]. We adopted the 50% heart rate reserve (HRR) task, which is considered to be a moderate-intensity exercise as per ACSM’s Guidelines for Exercise Testing and Prescription [ 37 ], and employed a previously-reported step exercise using a low-height bench [ 33 ]. For the former intensity, we calculated the target heart rate using the formula: …”
Section: Methodsmentioning
confidence: 99%
“…In recent years, moderate-intensity exercise has been also con rmed to improve cognitive and mental function [27,38], and it has been demonstrated that neurogenesis and neuroendocrine responses can be induced by not only high-intensity exercise but also moderate-intensity exercise [39,40]. Also in healthy young subjects, moderate-intensity exercise has been well assessed as an intervention to improve cognitive function [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Nakayama et al have reported a bench step exercise with a low height as an intervention to improve cognitive function [27]. The exercise has two advantages: rst, the low step (20 cm high) makes the execution safer and easier, and second, stairs can easily be substituted for the step, making it possible to perform the exercise indoors without being in uenced by the external environment.…”
Section: Exercise Interventionmentioning
confidence: 99%